Fluorescence and structure of methyl red-clay nanocomposites - Martynková, Grazyna Simha; Kulhánková, Lenka; Malý, Petr; Capková, Pavla (Journal of nanoscience and nanotechnology, 2008)
Two types of clay minerals-montmorillonite and vermiculite have been chosen as a host matrix for the intercalation of methyl red (MR) in order to investigate a possible fluorescence tuning via dye-clay interactions. The effect of silicate layer charge on the structure and fluorescence of dye-clay intercalated hybrid nanostructures was investigated using combination of molecular modeling with experiment. Structure of both intercalates MR-vermiculite (MR-VER) and MR-montmorillonite (MR-MMT) exhibits high degree of structural disorder resulting in broaden emission band. The fluorescence wavelength range of MR intercalated in clays is shifted to lower wavelengths compared with the pristine MR polycrystalline sample (800 nm). Results showed the strong dependence of fluorescence band maximum on the silicate layer charge, lambda(max) = 565 nm for MR-MMT, 645 nm for MR-VER and 800 nm for the methyl red fine crystalline powder, whereas the structural disorder in the arrangement of dye molecules affects the emission band broadening.
Keywords: Azo Compounds; povrchové vlastnosti; silikáty hliníku; Fluorescent Dyes; makromolekulární látky; Particle Size; Nanostructures; fluorescenční spektrometrie; testování materiálů; krystalizace; Models, Chemical; Aluminum Silicates; Materials Testing; Computer Simulation; nanostruktury; Clay; molekulární modely; molekulární konformace; Models, Molecular; Crystallization; Nanotechnology; velikost částic; Surface Properties; fluorescenční barviva; azosloučeniny; počítačová simulace; jíl; Molecular Conformation; Spectrometry, Fluorescence; Macromolecular Substances; chemické modely; nanotechnologie